The Benefits of Physical Activity for Patients with Cystic Fibrosis: A Literature Review - Julia Sieniawska; Angelika Kamizela; Magda Madoń; Patrycja Proszowska; Daria Sieniawska (Nicolaus Copernicus University in Toruń, 2024)
Introduction Cystic fibrosis (CF) is a complex and progressive genetic disorder that significantly impacts multiple organ systems, particularly the lungs and digestive tract. Despite advances in treatment and improved life expectancy, CF remains incurable, necessitating ongoing research and comprehensive management strategies. One of the key components in managing CF is the incorporation of physical activity (PA). Aim of the study The aim of the study is to investigate the role of physical activity in in the management of cystic fibrosis. Materials and methods This study underscores the critical role of physical activity (PA) in the management and overall well-being of individuals with cystic fibrosis (CF). It provides a comprehensive review of the multifaceted benefits of PA for CF patients, highlighting its positive impact on exercise tolerance, pulmonary function, cardiorespiratory fitness, muscle strength, and quality of life. PubMed and Google Scholar database was searched for articles written in English. The search included the keywords. Results The data suggest that while CF patients face unique challenges, including muscle weakness and exercise intolerance, regular PA can mitigate these effects and improve overall health outcomes. Supervised exercise programs have demonstrated significant improvements in exercise tolerance and respiratory muscle endurance without adverse effects, indicating their feasibility and safety for CF patients. Studies have shown that patients with CF who engage in regular PA experience slower declines in lung function, fewer hospitalizations, and better nutritional status. Specific types of exercise, such as anaerobic training, have been particularly effective in increasing muscle strength and body weight.